A rare case of uterus didelphys with full term pregnancy in left horn - Tuteja, Tanvi Vijay; Bendre, Kirti Rajesh; Niyogi, Geeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Uterus didelphys, also known as a duplicated uterus, is an embryological abnormality resulting from complete failure of fusion of Mullerian ducts causing full uterine development to erroneously occur bilaterally. It is associated with many obstetrical complications and thus has clinical importance. We present a case of an elderly patient with history of infertility diagnosed with uterus didelphys with a pregnancy in left horn. She carried pregnancy to term and delivered by caesarean section at 37 weeks of gestation. She had an uncomplicated intraoperative and postoperative period.